The Overview of Mean Arterial Pressure (MAP) Changes in Patients After General Anesthesia at Juanda Kuningan Hospital West Java: English - Pramudya Gurensky, Ganea; Sukmaningtyas, Wilis; Burhan, Asmat (Global Indonesia Health Care (GOICARE), 2023)
Purpose: to determine the description of changes in Mean Arterial Pressure (MAP) of patients after general anesthesia at Juanda Kuningan Hospital, West Java. Methods: This research is descriptive quantitative with a cross sectional approach. The sample in this study were all surgery patients with general anesthesia who met the criteria, while the sampling technique used was total sampling resulting in 100 respondents. Data analysis using univariate test. Findings: The results of the analysis showed that the most dominant age of respondents was early elderly (34%), with female gender (58%) and the most dominant Body Mass Index (BMI) was normal (91%). Normal MAP (70-100 mmHg) was obtained before induction of anesthesia as much as (77%), normal MAP (70-100 mmHg) after general anesthesia in the recovery room as much as (93%%). Conclusions: These results describe that changes in MAP values after general anesthesia can occur and the majority of pre-induction anesthesia MAP values of respondents will experience a decrease in MAP values during post-general anesthesia in the recovery room. So it is very important to maintain normal MAP values (70-100 mmHg) so as to reduce the risk of postoperative complications that can occur in patients.